Estimation the heterosis and combining ability for some chemical characteristics of different tobacco varieties (Nicotiana tabacum L.) (Journal of Hama University, 2024)
The experiment was carried out during the two seasons in the years 2021-2023 in a nursery at the Faculty of Agriculture, Tishreen University, Lattakia, Syria, In the first season the three tobacco parents (Nicotiana tabacum L.) (Prilep (G1), Basma(G2), and Baladi (G3)) were evaluated. A half-diallel mating design was made between different genotypes of tobacco.The F1 hybrids were planted with their parents according to a randomized complete block design with three replicates, to estimate the heterosis for the average parent and the best parent, and the general (G.C.A) and specific (S.C.A) combining ability, and nature of gene action for: Chlorophyll, carotenoids, phosphorus and phenols.Genetic analysis showed the importance of additive and dominant effects on the heredity of all characteristics. The variance ratio of general combining ability to specific combining ability was greater than 1 for all studied traits.The G1 parent exhibited a highest GCA for Chlorophyll and Carotenoids Content. However, the G3 parent exhibited a highest GCA for Poly Phenoles content, followed by G2 parent for Phosphorus and Poly Phenoles content.The hybrid G1 × G3 exhibited the highest SCA for Corophyll and Carotenoids Content, while the G1 × G2 exhibited the lower percentage of phosphorus content in leaves. However, the G2 × G3 exhibited the highest SCA for Phenoles content, with the highest values for heterosis for the studied characteristics.